2004
DOI: 10.1016/j.brainres.2004.05.036
|View full text |Cite
|
Sign up to set email alerts
|

Progressive plastic changes in the hand representation of the primary motor cortex parallel incomplete recovery from a unilateral section of the corticospinal tract at cervical level in monkeys

Abstract: After a sub-total hemi-section of the cervical cord at level C7/C8 in monkeys, a paralysis of the homolateral hand is rapidly followed by an incomplete recovery of manual dexterity, reaching a plateau after about 40-50 days, whose extent appears related to the size of the lesion. During a few days after the lesion, the hand representation in the contralateral motor cortex disappeared, replaced by representations of either face or more proximal body parts. Later, however, following a time course (about 40 days)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
98
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(105 citation statements)
references
References 36 publications
6
98
1
Order By: Relevance
“…The manual dexterity performances were assessed for several months post-lesion, until the animals reached a plateau reflecting a stable level of manual dexterity. The behavioural, electrophysiological and neuroanatomical tracing data related to the CS tract derived from these animals were described in previous reports (Freund et al, , 2007Schmidlin et al, 2005Schmidlin et al, , 2004Wannier et al, 2005). The present report is focussed on anatomical aspects dealing specifically with the issue of fate of RS neurons after unilateral cervical section.…”
Section: Methodsmentioning
confidence: 95%
See 3 more Smart Citations
“…The manual dexterity performances were assessed for several months post-lesion, until the animals reached a plateau reflecting a stable level of manual dexterity. The behavioural, electrophysiological and neuroanatomical tracing data related to the CS tract derived from these animals were described in previous reports (Freund et al, , 2007Schmidlin et al, 2005Schmidlin et al, , 2004Wannier et al, 2005). The present report is focussed on anatomical aspects dealing specifically with the issue of fate of RS neurons after unilateral cervical section.…”
Section: Methodsmentioning
confidence: 95%
“…All animals included in the present study belong to a long-term research project on spinal cord lesion from which post-lesion changes in the CS system were described earlier (Freund et al, , 2007Schmidlin et al, 2005Schmidlin et al, , 2004Wannier et al, 2005). To assess the number of RS neurons in this model, midbrain sections including the red nucleus were obtained from 15 adult (3-8 years old) macaque monkeys (Macaca mulatta or Macaca fascicularis).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes include shrinkage of the cortical representation synonymous with the area of injury (Toldi et al 1996), the corresponding area in the uninjured cortex and invasion of adjacent territory by neighbouring representations (Nudo et al 1997). This motor cortical reorganisation can be influenced by training tasks and studies have shown that functional recovery mirrors further cortical reorganisation (Nudo et al 1996, Liepert et al 2000, Schmidlin et al 2004). …”
Section: Introductionmentioning
confidence: 99%